Modeled Centennial Ocean Warming in the Amundsen Sea Driven by Thermodynamic Atmospheric Changes, Not Winds - K. A. Turner; K. A. Naughten; P. R. Holland; A. C. Naveira Garabato (Geophysical Research Letters, 2025)
Abstract Increased ice shelf melting caused by ocean warming in the Amundsen Sea is likely committed for the coming century. However, the drivers behind this projected ocean warming are not yet fully understood. Using a high‐resolution regional model, we compare future projections of the Amundsen Sea under the RCP8.5 scenario against pre‐industrial projections. The two ensembles differ measurably between 2013 and 2018, and continue to diverge under high‐emissions forcing. We conduct two more experiments separating the effects of stronger, poleward‐shifted winds against a warmer, wetter atmosphere (defined here as atmospheric thermodynamics). We run experiments that use RCP8.5 winds and pre‐industrial thermodynamics, and vice versa. We find that atmospheric thermodynamic change modulates Circumpolar Deep Water inflow onto the shelf, making thermodynamic change the primary driver of ocean warming on the continental shelf on centennial timescales.